The Effect of GDP and Credit Interest on the Average Income of Indonesians during the Pandemic - Francisca Sestri Goestjahjanti (Politeknik Negeri Semarang, 2021)
This research has an important goal of discussing the effect of GDP and credit interest rate on the average income of Indonesian people during the pandemic. Hypothesis testing is carried out according to the provisions of the use of explanatory research methods that explain the causal relationship between the predicting and the predicted variables. Linear regression is a form of analytical technique in this study for processing, analyzing secondary time series data in 2008 - 2020, for 13 years. The results of this study through hypothesis test, there is a significant positive effect between GDP on average income, and there is a significant negative effect on credit interest on the average income of Indonesian people, and simultaneously, there is a significant effect of 97.10 percent between GDP and credit interest rate on the average income of the Indonesian people during the pandemic.